INSIDENSI NYERI PUNGGUNG BAWAH PADA TENAGA KESEHATAN DI RUMAH SAKIT INDONESIA : Tinjauan Pustaka - Tan, Ashley Juan; Sakasasmita, Steven; Febrian, Reynard (Jurnal MedScientiae, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal complaints among healthcare workers, potentially reducing productivity and the quality of hospital services. In Indonesia, data regarding the incidence of LBP among healthcare workers remains limited.This study is a systematic literature review following the PRISMA 2020 guidelines. Articles were retrieved from Google Scholar and Garuda databases, focusing on publications from 2016 to 2025. Inclusion criteria consisted of studies discussing LBP among healthcare workers in Indonesian hospitals. Case reports, cohort studies, meta-analyses, and narrative reviews were excluded. A total of 1,110 articles was identified, and after the selection process, 10 articles met the criteria. The majority of studies used a cross-sectional method and questionnaire instruments to measure the incidence and risk factors of low back pain (LBP). The average incidence of LBP among healthcare workers, particularly nurses, identified the main risk factors as age, gender, years of service, working hours, and working posture. It was estimated around 37,3% to 86,6% case of LBP incidence among healthcare workers in Indonesia. Preventive measures, such as ergonomic education and workplace modifications, are recommended to reduce the risk and negative impacts of LBP in hospital settings.